A preliminary study of natural environmental change and its impact on early Late Paleolithic people in the northeast central Korean Peninsula during Marine Istope Stage 3 (40–30k cal a bp). (21st September 2021) - Yi, Sangheon; Han, Chang‐Gyun; Oh, Keun‐Chang; Seo, In Sun; Kim, Dongwook; Lee, Jaeyoung; Han, Min; Choi, Hanwoo; Lim, Jaesoo; Park, Sujeong; Jun, Chang‐Pyo; Cho, Taesop
ABSTRACT: We comprehensively analyzed sediments obtained from an archeological excavation. A trench sediment profile of Maedun Cave (MC), South Korea, was analyzed geoarchaeologically. Multi‐proxy analyses (palynomorphs, grain size, magnetic susceptibility, animal bones and artifacts) reflected the vegetation, hydroclimate and lives of prehistoric people at Marine Isotope Stage (MIS) 3 (ca. 40–30k cal a bp ) in the early Late Paleolithic. The palynoflora consisted of pollen and non‐pollen palynomorphs. Under the air‐circulation system in the cave, anemophilous pollen flowed in during the day, whereas waterborne pollen and spores, and freshwater algae, were transported by flooding during the summer monsoon rainy season. Mixed conifer and deciduous broad‐leaved forest with an understory of pteridophytes flourished around the north‐east central Korean Peninsula during MIS 3. Freshwater algae and grass pollen records may reflect precipitation intensity. It is assumed that they had flowed in during flooding caused by high precipitation during the enhanced East Asian summer monsoon, corresponding to Dansgaard–Oeschger (D/O) events 5 and 8 of δ 18 O GISP2 and Hulu Cave. The prehistoric people hunted herbivorous animals in the area around MC and sheltered inside it seasonally. They also used the grains of oats growing near the dwelling as a source of food. Highlights: Multi‐proxy records from cave sediments of the Korean Peninsula shed light on vegetation cover and climate conditions during MIS 3 (40–30k cal a BP). Herbaceous pollen and non‐pollen palynomorphs flowed into the cave due to flooding caused by high precipitation under the enhanced East Asia summer monsoon. Fossilized mammal bones and artifacts shed light on the lifestyle of prehistoric people in the early Late Paleolithic. Geoarchaeological evidence provides insight into the responses of ancient societies to climate conditions in northeast central Korea.